How Social Accountability and Community Support Affect Local Human Resources' Perceptions of the Sustainability of the Palm Oil Industry in Indonesia? - Judijanto, Loso (West Science Social and Humanities Studies, 2025)
This study investigates how social accountability and community support influence local human resources’ perceptions of sustainability in Indonesia’s palm oil industry. Using a quantitative approach, data were collected from 120 respondents representing employees, supervisors, and community liaisons in major palm oil-producing regions. All constructs were measured using a five-point Likert scale, and data were analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS 3) to test the proposed relationships. The results show that both social accountability (β = 0.46; p < 0.001) and community support (β = 0.39; p < 0.001) significantly enhance sustainability perception, explaining 64% (R² = 0.64) of the variance. Social accountability strengthens perceptions through transparency, ethical disclosure, and responsiveness, while community support reinforces trust, participation, and local cooperation. The findings highlight that sustainable development in the palm oil sector relies not only on environmental compliance but also on social governance and collective responsibility. The study contributes to theory by integrating Stakeholder Theory and the Theory of Planned Behavior, providing empirical evidence that sustainability perception is shaped by institutional accountability and social interaction within local communities.